No Fire Next Time : Black-Korean Conflicts and the Future of America's Cities - Joyce, Patrick D. (Book collections on Project MUSE., 2003)
Why did Black-Korean tensions result in violent clashes in Los Angeles but not in New York City? In a book based on fieldwork and on a nationwide database he constructed to track such conflicts, Patrick D. Joyce goes beyond sociological and cultural explanations. "No Fire Text Time shows how political practices and urban institutions can channel racial and ethnic tensions into protest or, alternatively, leave them free to erupt violently. Few encounters demonstrate this connection better than those between African Americans and Korean Americans. Cities like New York, where politics is noisy, contentious, and involves people at the grassroots, have seen extensive Black boycotts of Korean-owned businesses (usually small grocery stores). African Americans in Los Angeles have sustained few long-term boycotts of Korean American businesses--but the absence of "routine" contention there goes hand in hand with the large-scale riots of 1992 and continuous acts of individual violence. In demonstrating how conflicts between these groups were intimately tied to their political surroundings, this book yields practical lessons for the future. City governments can do little to fight widening economic inequality in an increasingly diverse nation, Joyce writes. But officials and activists can restructure political institutions to provide the foundations of new multiracial coalitions.